Novel microbial-mediated modifications of woo - Queiroga, A. Catarina (2010)
A total of 158 microbial strains, previously isolated from raw wool samples of Portuguese Merino breed of sheep, were screened for extracellular protease activity. The 12 isolates with the highest overall activity were further tested via incubation in nutrient broth, and assaying of cell-free supernatants using casein as substrate protein. The cell-free supernatants of the three isolates exhibiting the best performance were finally tested on knitted wool using bursting strength and area shrinkage as quantitative parameters, and microstructure using scanning electron microscopy as qualitative parameter, to conclude on their putative role upon the fiber features. The aforementioned three isolates produced lower weight loss and area shrinkage than those brought about by a commercial reference enzyme under similar operating conditions, without significantly loosing bursting strength.